Biodiversity gains can be achieved with coastal wetland restoration for plants, invertebrates, birds, and bats - Valerie Hagger; Mathew A Vanderklift; Kieren P. Beaumont; Andrew Olds; Sabine Dittman; Catherine E. Lovelock (Ecological Indicators, 2025)
The world’s coastal ecosystems have experienced significant biodiversity declines. Restoration of coastal wetlands that enhances biodiversity is needed for the conservation of the unique flora and fauna depending on these ecosystems. Verification of biodiversity benefits to accompany carbon credits or to generate separate biodiversity credits under emerging nature markets is fundamental to the success of coastal wetland restoration. While there are many approaches to assess biodiversity in coastal wetland ecosystems, species assessed and metrics have not yet been standardised for coastal wetland restoration. We aimed to identity taxonomic groups and metrics that represent biodiversity recovery and develop an approach to quantify biodiversity gains from restoration of coastal wetlands relative to local, native reference ecosystems. We developed and tested a set of indicators and survey methods to quantify specific elements of biodiversity in mangroves, saltmarshes and supratidal forests in two coastal wetland restoration projects from different climatic regions in Australia. We measured and assessed vegetation and habitat structure and composition, and fauna community characteristics of benthic macroinvertebrates, birds, and insectivorous bats. We developed an area-adjusted multi-diversity index for each restoration site based on selected indicators for different vegetation types along a tidal elevation gradient. Indicators that have linear restoration trajectories were selected. Modelling of restored vegetation types considering historic environmental changes and future tidal inundation was needed to define reference ecosystems. The multi-diversity index for the partially-restored site at the Blue Heart in Queensland was almost double that of the pre-restoration site at Webb Beach in South Australia, because of the larger extent and better condition of current vegetation types in comparison to local reference ecosystems. Plant species composition, species richness in functional groups of birds and bats, bat activity in functional groups, and benthic macroinvertebrate species diversity are promising metrics that could be refined as indicators for a standardised biodiversity method for coastal wetland restoration that could inform biodiversity crediting.